Epigenetic modification of cytosines fine tunes the stability of i-motif DNA - Wright, Elisé P (Nucleic Acids Res, 2020)
i-Motifs are widely used in nanotechnology, play a part in gene regulation and have been detected in human nuclei. As these structures are composed of cytosine, they are potential sites for epigenetic modification. In addition to 5-methyl- and 5-hydroxymethylcytosine modifications, recent evidence has suggested biological roles for 5-formylcytosine and 5-carboxylcytosine. Herein the human telomeric i-motif sequence was used to examine how these four epigenetic modifications alter the thermal and pH stability of i-motifs. Changes in melting temperature and transitional pH depended on both the type of modification and its position within the i-motif forming sequence. The cytosines most sensitive to modification were next to the first and third loops within the structure. Using previously described i-motif forming sequences, we screened the MCF-7 and MCF-10A methylomes to map 5-methylcytosine and found the majority of sequences were differentially methylated in MCF7 (cancerous) and MCF10A (non-cancerous) cell lines. Furthermore, i-motif forming sequences stable at neutral pH were significantly more likely to be epigenetically modified than traditional acidic i-motif forming sequences. This work has implications not only in the epigenetic regulation of DNA, but also allows discreet tunability of i-motif stability for nanotechnological applications.